Edukasi Pemanfaatan TikTok Sebagai Media Bisnis Digital di Desa Rejosari Rt 03 Rw 07, Karanggeneng, Kabupaten Boyolali - M. Ragil Jibran; Nangga Andrisa; Mustofa Kurniawan; Jalu Ahda Adiananta; Fauzi Indra Kurniawan; Unna Ria Safitri (Lembaga Pengembangan Kinerja Dosen, 2026)
This community service programme aims to provide education and training on the utilisation of the TikTok application as a digital business medium for the community of Rejosari Village, RT 03 RW 07, Karanggeneng, Boyolali Regency. The rapid development of digital technology and social media has transformed patterns of economic interaction from conventional systems into platform-based digital economies. Nevertheless, at the village level, the use of social media remains predominantly oriented towards entertainment and has not yet been optimally directed as an instrument for enhancing household economic capacity. The implementation method adopts an educative–participatory approach through the delivery of conceptual materials, demonstrations of TikTok features, and hands-on practice in creating digital business content. The results of the activity indicate an improvement in participants’ understanding of social media–based digital business opportunities, as well as the emergence of collective awareness to utilise TikTok as a means of generating additional income. This programme confirms that social media–based digital business education can function as an effective instrument for empowering rural communities in responding to digital economic transformation.